Seabuckthorn seed protein concentrate: a novel seed protein; emulsifying properties as affected by ultrasonication and enzymatic hydrolysis. (3rd August 2022) - Khan, Zakir Showkat; Sodhi, Navdeep Singh; Fayaz, Shemilah; Wani, Sajad Ahmad; Bhat, Mohammad Sayeed; Mishra, Hari Niwas; Bakshi, Rayees Ahmad; Dar, B. N.; Dhillon, Bhavnita
Summary: The study investigated the influence of ultrasonication and enzymatic hydrolysis on emulsifying properties of Seabuckthorn seed protein concentrate (SSPC). Sonication was done at 24 kHz (50% amplitude) for different time combinations (15, 45 and 75 min), and enzymatic hydrolysis of SSPC was done using pepsin, trypsin and protamex, resulting in different SSPC emulsions. All the emulsions were characterised to ascertain the particle size distribution, pH stability, temperature stability and rheology. Hydrolysed SSPC was also characterised for the respective degree of hydrolysis by pepsin, trypsin and protamex. The pepsin revealed the highest degree of hydrolysis among the proteases, followed by trypsin and protamex. The ultrasonicated SSPC and SSPC hydrolysate emulsions showed unimodal particle size distribution except for pepsin hydrolysate emulsions which showed bimodal size distribution of particles. The variation in pH from 2 to 5 increased the particle size, while at higher pH (7–10), the particle size decreased for all the emulsions. The increase in temperature from 25°C to 85 °C increased the droplet size of all the emulsions except for protamex at 75 min, which showed a relatively smaller droplet size than other proteases. All the emulsions displayed shear thinning behaviour, however, the pepsin‐treated emulsions showed the highest consistency index and K‐value. The resulting ultrasonicated and different protease‐treated SSPC emulsions can be suitable green and nontoxic alternatives to synthetic emulsifiers used in the food industry. Abstract : Seabuckthorn berries, seeds and leaves have immune‐modulating, cardioprotective, antiatherogenic, antiradiation, anti‐inflammatory, antidiabetic, anticarcinogenic, and hepatoprotective benefits, thus have the potential to be used in the food industry as a functional ingredient. Ultrasonication and enzymatic hydrolysis lead to better emulsifying properties of SSPC as compared to native SSPC. SSPC emulsions can be used as a non‐toxic alternative to synthetic emulsions.